Risk Factors Distribution for Cardiovascular Diseases among High School Students - Jawad Ashraf, Iqtidar-Ud-Din, Muhammad Abdur Rauf, Yasir Arafat, Imran Khan, Tanveer Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Cardiovascular diseases (CVDs) are the chronic non-communicable diseases and leading cause of mortality due to various risk factors such as diabetes, tobacco usage, hypertension, obesity, dyslipidemia, and physical inactivity. The incidence of CVDS is rising rapidly due to these risk factors. These risk factors track at different ages starting from childhood to adulthood and their distribution varies with gender. Therefore, the prevalence of these risk factors among high school students need to be determined. The present study aimed to assess the different risk factor’s distribution for cardiovascular diseases. Methodology: This cross-sectional study was carried out among 940 high school students (aged 12-18 years) of Nowshera Pakistan from September, 2020 to December, 2021. Random sampling technique and WHO steps methodology was used for the assessment of various risk factors. All the randomly selected participants were recruited conventionally. Descriptive statistics was used to measure the risk factors distribution among high school students. SPSS version 24 was used for data analysis. Results: The overall mean age of the students was 15.8±1.4 years whereas age varied from 12 years to 18 years. Of the total 940 students, about 59% (n=555) were boys and 41% (n=385) were girls. The prevalence of tobacco, overweight, and hypertension among boys were 33.2%, 12.1%, 7.2%, and 17.6% (P< 0.001) respectively. However, their prevalence among girls were 7.1%, 1.4%, 12.2%, and 23.8% (P<0.001) respectively. The hypercholesterolemia was found higher among boys whereas girls had more prevalent high triglycerides levels compared to boys. Conclusion: The present study found a higher incidence of risk factors for cardiovascular diseases among high school students. These risk factors need to be reduced to control cardiovascular diseases among the young population. Also, this study found a poor profile of various risk factors for cardiovascular disease that require future nation-wide investigation to clarify the precise findings. Keywords: Cardiovascular disease, Risk factors, Hypertension